Customer Service For Hospitality And Tourism - Hudson, Simon; Hudson, Louise (2013)
The 'whys' and 'hows' of customer service. Easy to read, very current, and full of references to all the latest research. Chapters cover financial and behavioural consequences of customer service, consumer trends, developing and maintaining a service culture, managing service encounters, CRM and much more.
Includes QR codes.
Includes bibliographical references and index.
Keywords: Hospitality industry -- Customer services; Tourism; Customer services; Travel and Tourism